Metabolism and Tissue Distribution of Chelerythrine and Effects of Macleaya Cordata Extracts on Liver NAD(P)H Quinone Oxidoreductase - Huang, Chong-Yin; Huang, Ya-Jun; Zhang, Zhuo-Yi; Liu, Yi-Song; Liu, Zhao-Ying (Frontiers in Veterinary Science, 2021)
Background:Macleaya cordata (Willd.) (Papaveraceae) is listed as a feed additive in animal production by the European Food Authority. Methods: The metabolites of chelerythrine in rats were measured in vitro and in vivo by rapid and accurate high-performance liquid chromatography/quadrupole-time-of-flight mass spectrometry (HPLC/QqTOF-MS). The structures of CHE metabolites were elucidated by comparing their changes in accurate molecular masses and fragment ions with those of parent ion or metabolite. The metabolic enzymes that were involved in chelerythrine reduction were investigated using an inhibition method. The tissue distribution of chelerythrine and the effects on NQO1 following intragastric administration with M. cordata extracts in rats were examined. Results: A total of twelve metabolites of chelerythrine were characterized by this approach in rat liver S9 and in vivo. The reduction of the iminium bond of chelerythrine and subsequent O-demethylation was the main metabolic pathway of chelerythrine in rat liver S9 while the reduction of the iminium bond of chelerythrine was the main metabolic pathway of chelerythrine in rats in vivo. After the rats were given intragastric administration, the low concentration residues of sanguinarine and chelerythrine in different rat tissues were found at 48 h after the last dose, suggesting that both compounds could be widely distributed in tissues. The results also indicated that XO, NQO1, NQO2, and carbonyl reductase are involved in chelerythrine reduction. Macleaya cordata extracts treated female and male rats, respectively, showed different responses, inhibiting NQO1 activity in males, but inducing NQO1 activity in females. Chelerythrine had a weak impact on NQO1 activity, but sanguinarine inhibited NQO1 activity Conclusion: Through studying the effects of cytosolic reductase inhibitors on chelerythrine reduction and the impact of chelerythrine and sanguinarine on the activity of NQO1 in vitro and in vivo, we clarified the potential drug interaction of Macleaya cordata extract in clinical application, so as to provide theoretical guidance for clinically safe medication. In addition, it provided a reference basis for the metabolic mechanism of chelerythrinein rats.